Dilema Kebijakan Pengelolaan Hutan di Indonesia - Moh. Rif'an (CV Rewang Rencang, 2020)
The history of community-based land use is a real and factual reality that can be seen from the past and present. Basically, the study of forest policy will not be far from understanding the relationship between the ruler (regulator), forest and society, which can be seen in two aspects, namely juridical and sociological. In the study of juridical aspects, it has been arranged in the legal framework that people who have a related right to forest (to customary forests or forest rights) obtain their legal status and must be protected over it. Such conditions are adjusted in Law No. 41 of 1999 on Forestry. While in the perspective of sociological aspects, forests and communities cannot be separated on the basis of forests as one of the buffers of life and prosperity of communities whose existence must be maintained optimally. But unfortunately, the small number of state activities reflected from forest management practices to article by article of Ministerial Regulations to The Law in the Constitutional Court's Decision reflects a dilemma in forest management. Departing from the understanding that the state in the behavior of the government to the district / city level is able to take the potential of forest resources constitutionally without reducing the rights of the community that leads to triggering systemic conflicts.